Foreign and domestic investors and tax induced ex-dividend day trading - Liljeblom, Eva; Löflund, Anders; Hedvall, Kaj (Journal of Banking & Finance, 2001)
This paper reports evidence on the consequences of differential tax treatment for domestic and foreign owners in a market with a high degree of foreign ownership for certain stocks, the Helsinki Stock Exchange (HSE). We find that ex-dividend day ratios vary with the degree of foreign ownership, and detect significantly abnormal ex-dividend day trading volumes. The average ex-dividend price drops for high-yield, high-foreign ownership stocks are likely to lie outside no-arbitrage boundaries for domestic taxable investors. An investigation of short selling through a derivatives instrument also reveals significant excess trading volumes in ex-dividend months. The tax heterogeneity of the company's ownership structure seems to play a role in explaining deviations from dividend neutrality, more deviations are observed for companies with a more homogeneous ownership structure in terms of taxation.